The Application of Big Data on The Performance of MSME Businesses in Batam City - Bahar, Hardi; Ayuningtyas, Ni Putu Winda; Lubis, Syarif Hidayah (Pusat P2M Politeknik Negeri Batam, 2023)
This study investigates the influence of Big Data implementation on the business performance of Micro, Small, and Medium Enterprises (MSMEs) in Batam City. The research examines three characteristics of Big Data